2022
DOI: 10.3390/pr10050920
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Horizontal Gas–Liquid Segregated Flow Regimes with an All Flow Regime Multifluid Model

Abstract: The generalized multifluid modelling approach (GEMMA) has been developed to handle the multiplicity of flow regimes and the coexistence of interfaces of largely different scales in multiphase flows. The solver, based on the OpenFOAM reactingEulerFoam family of solvers, adds interface resolving-like capabilities to the multifluid solver in the cells occupied by large interfaces. In this paper, GEMMA is further developed to predict stratified and slug flow regimes in horizontal ducts. The suppression of the turb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 34 publications
(67 reference statements)
0
6
0
Order By: Relevance
“…The approach is tested for various multiphase scenarios: an ethanol droplet in equilibrium, a dam break, a rising gas bubble, a dispersed flow in a vertical pipe, and a plunging liquid jet. The model is further verified for stratified and slug flow regimes by Colombo et al 14 Overall a significant over-estimation of the interfacial shear stress is observed, which is attributed to the interfacial momentum transfer modeling. Especially, the interfacial drag modeling at resolved interfaces is the key to high accuracy in that context.…”
mentioning
confidence: 66%
See 3 more Smart Citations
“…The approach is tested for various multiphase scenarios: an ethanol droplet in equilibrium, a dam break, a rising gas bubble, a dispersed flow in a vertical pipe, and a plunging liquid jet. The model is further verified for stratified and slug flow regimes by Colombo et al 14 Overall a significant over-estimation of the interfacial shear stress is observed, which is attributed to the interfacial momentum transfer modeling. Especially, the interfacial drag modeling at resolved interfaces is the key to high accuracy in that context.…”
mentioning
confidence: 66%
“…In detail, in the buoyancy term r 𝛼 g i 𝜌 𝛼 , that is, in the third term on R.H.S. of Equation ( 2), for each phase sharing the large scale interface the phase-specific density 𝜌 𝛼 is replaced by mixture density 𝜌, which is defined analogously to Equation (14). With that change, the proposed gravity term in Equation ( 2) reads:…”
Section: Under-resolving Drag Model With Buoyancy Modificationmentioning
confidence: 99%
See 2 more Smart Citations
“…It was the first time it was adopted for centrifugal pump flow and certainly leaves potential for further improvements. In the literature, more sophisticated hybrid multiphase approaches have been reported, such as the generalized multiphase modeling approach (GEMMA) of De Santis et al and Colombo et al [73,143,144] and the hybrid multi-scale model of Meller et al [79]. The GEMMA model fundamentally deviates from the one described here by including an interfacial drag formulation for large-scale interfaces, which was first proposed by Marschall [75] within the EE2F framework.…”
Section: Hybrid Two-phase (H2p) Approachmentioning
confidence: 98%